Delivery in water, experience in a population of Mexican women in Mexico City - Luján-Irastorza Jesús Estuardo; Durand-Montaño Carlos; Hernández-Ramos Roberto; Ávila-Pérez Felipe de Jesús; Ávila-Rebollar Daniela; Valdez-Chávez Teresita de Jesús; Silva-Meléndez Jorge; Yáñez-González Marco Antonio; García-Cruz Valeria; Loof-Esquivel Mónica; Beltrán-Tapia José Luis; Peñalva-Rosales Samuel Octavio; et al. (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2021)
Background: Labor is a physiological process during which the fetus, the membranes, the umbilical cord, and the placenta are expelled from the uterus and water delivery has become popular, although its prevalence is unknown, it is supported by healthy women with full-term pregnancies, without complications; although there is insufficient evidence to support or discourage it. Objective : To identify obstetric and neonatal outcomes and complications in women who delivered in water and to compare them with traditional deliveries. Material and methods: It is a retrospective, observational and cross-sectional study, where 2486 women were included from a database of 4223 women assisted from 2004 to 2020 in private hospitals; Of the 2486 patients included, 1025 had a water delivery and 1461 had a conventional delivery, discarding 1737 women who underwent caesarean section from the study. The information obtained from the patients, their data obtained for this study were kept in the anonymity of the patients, where they were analyzed: non-parametric data reported in percentages using Chi-square ; Parametric, perinatal and neonatal data are reported as mean plus Standard Deviation (± SD) and analyzed using Student's T, using the SPSS version 25 statistical package. Results: A total of 2486 women were included in this study, the birth in 1025 was water delivery (24%) and 1461 was conventional delivery (35%), 1737 caesarean section (41%) were excluded from the study, no difference was observed maternal age; unlike weight, height, body mass index; they were higher in women with water birth compared to conventional. No difference was demonstrated between nulliparous (45.99%) and multiparous (53.86%) when comparing both births  in water and conventional; only increase in previous cesarean sections (9.36 vs 6.5%, p = 0.008) and decrease in previous abortions (16.19 vs 20.94%, p = 0.002) in water delivery with the conventional one; complications were not different: administration of oxytocin (3.2 vs 3.1) or postpartum hemorrhage (0.29 vs 0.13) in both deliveries; no differences in first degree perineal tears (21.4 vs 18.5%); Only for the second and third-degree  was it greater in conventional delivery than in water delivery (6.6 vs 11.4%, p = 0.00), (0 vs 2.8%) respectively, only 1.9% of deliveries in water that required epidural block ended in delivery conventional. Conclusion : Water birth reduces stress, pain sensation, second and third-degree  perineal lacerations and contributes to better newborn outcomes; the selection and inclusion of patients with low-risk pregnancies allow  better perinatal results than conventional delivery; but, further studies are required to use it routinely.